Functional muscle ischemia in Duchenne and Becker muscular dystrophy - Thomas, Gail D. (Frontiers in Physiology, 2013)
Duchenne and Becker muscular dystrophy (DMD/BMD) comprise a spectrum of devastating X-linked muscle wasting disease for which there is no treatment. DMD/BMD is caused by mutations in the gene encoding dystrophin, a cytoskeletal protein that stabilizes the muscle membrane and also targets other proteins to the sarcolemma. Among these is the muscle-specific isoform of neuronal nitric oxide synthase (nNOSµ) which binds spectrin-like repeats within dystrophin’s rod domain and the adaptor protein α-syntrophin. Dystrophin deficiency causes loss of sarcolemmal nNOSµ and reduces paracrine signaling of muscle-derived nitric oxide (NO) to the microvasculature, which renders the diseased muscle fibers susceptible to functional muscle ischemia during exercise. Repeated bouts of functional ischemia superimposed on muscle fibers already weakened by dystrophin deficiency result in use-dependent focal muscle injury. Genetic and pharmacologic strategies to boost nNOSµ-NO signaling in dystrophic muscle alleviate functional muscle ischemia and show promise as novel therapeutic interventions for the treatment of DMD/BMD.